The Development of an E-book Guide to Traditional Games for Kindergarten B Teachers in Preventing Bullying - Markus Apriadi Joko Prakoso; Ika Budi Maryatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The number of bullying cases involving early childhood with peers in schools increased from 2023 to 2024. The purpose of this study is to produce a complete e-book construct, “traditional game guide for kindergarten B teachers in preventing bullying through the role of bystanders,” that is feasible and practical for users. This study uses the ADDIE development method (Analyze, Design, Develop, Implement, Evaluate). The field trial score was 4.5 (Very Practical). The results of this study indicate that the product is Very Feasible based on validation results from media and material experts, and is considered Very Practical for kindergarten teachers, who are the product users and research samples in field trials. The product is considered capable of supporting teachers in preventing bullying from an early age in schools through traditional games that instill social awareness, especially by empowering bystanders.